The effect of esketamine in patients with treatment‐resistant depression with and without comorbid anxiety symptoms or disorder. Issue 11 (22nd July 2021) - Daly, Ella J.; Turkoz, Ibrahim; Salvadore, Giacomo; Fedgchin, Maggie; Ionescu, Dawn F.; Starr, H. Lynn; Borentain, Stephane; Trivedi, Madhukar H.; Thase, Michael E.; Singh, Jaskaran B.
Abstract: Background: Comorbid anxiety is generally associated with poorer response to antidepressant treatment. This post hoc analysis explored the efficacy of esketamine plus an antidepressant in patients with treatment‐resistant depression (TRD) with or without comorbid anxiety. Methods: TRANSFORM‐2, a double‐blind, flexible‐dose, 4‐week study (NCT02418585), randomized adults with TRD to placebo or esketamine nasal spray, each with a newly‐initiated oral antidepressant. Comorbid anxiety was defined as clinically noteworthy anxiety symptoms (7‐item Generalized Anxiety Disorder scale [GAD‐7] score ≥10) at screening and baseline or comorbid anxiety disorder diagnosis at screening. Treatment effect based on change in Montgomery–Åsberg Depression Rating Scale (MADRS) total score, and response and remission were examined by presence/absence of comorbid anxiety using analysis of covariance and logistic regression models. Results: Approximately 72% (162/223) of patients had baseline comorbid anxiety. Esketamine‐treated patients with and without anxiety demonstrated significant reductions in MADRS (mean [SD] change from baseline at day 28: −21.0 [12.51] and −22.7 [11.98], respectively). Higher rates of response and remission, and a significantly greater decrease in MADRS score at day 28 were observed compared to antidepressant/placebo, regardless of comorbid anxiety (with anxiety: difference in LS means [95% CI] −4.2 [−8.1, −0.3]; without anxiety: −7.5 [−13.7, −1.3]). There was no significant interaction of treatment and comorbid anxiety ( p = .371). Notably, in the antidepressant/placebo group improvement was similar in those with and without comorbid anxiety. Conclusion: Post hoc data support efficacy of esketamine plus an oral antidepressant in patients with TRD, regardless of comorbid anxiety.